Studi komparasi hasil belajar siswa sebelum dan sesudah penggunaan bahan ajar IPA terpadu bermuatan literasi saintifik tema pemanfaaatan tekanan kelas VIII SMPN 31 Padang - Devi Permata Sari; Asrizal Asrizal; Gusnedi Gusnedi; fatni mufit (PILLAR OF PHYSICS EDUCATION, 2019)
Education in the 21st century is intended to create people who have the knowledge and skills to survive in the globalization era. Integrated science teaching in the 2013 curriculum should be implemented in an integrated form, including Physics, Biology, and Chemistry. Integration in science teaching is intended to make teaching more meaningful, practical, and realistic, so that it can improve the learning outcomes of students. However, the implementation of integrated science teaching was not in accordance with the expected condition. The solution to the problem was to use integrated science teaching material with scientific literacy. The objective of the research was to investigate the effect of the use of the integrated science teaching material with scientific literacy on the theme of the use of pressure in the scientific approach to the learning outcomes of class VIII SMPN 31 Padang. This type of research was a quasi-experimental research with a before and after design. The research population was all class VIII students of SMPN 31 Padang in academic Year 2018/2019. By using a purposive sampling technique, it was obtained class VIII 5 students as the research sample. The research instrument consisted of a multiple choice written test sheet to assess knowledge, a performance assessment sheet for assessing skills, and an observation sheet to assess attitudes of students. Data analysis techniques included descriptive statistics analysis, normality test, homogeneity test, and paired comparison test. Based on the result of data analysis, it can be stated that the use of Integrated science teaching material with scientific literacy has a significant difference in learning outcomes of students between before and after they used it on the theme of the use of pressure in class VIII of SMPN 31 Padang. This difference in learning outcomes indicated that the use of integrated science teaching material with scientific literacy on the theme of the use of pressure has a significant effect on the three aspects of learning outcomes of students, including knowledge in scientific contexts and scientific concepts of literacy, scientific processes of literacy, and attitude of students.